Physical Cue Influences Children’s Empathy for Pain: The Role of Attention Allocation - Yan, Zhiqiang; Pei, Meng; Su, Yanjie (Frontiers in Psychology, 2018)
Empathy for pain is evolutionally important and context-dependent. The current study explored the effect of physical cue on 4- to 5-year-old children’s empathy for pain with two experiments. Experiment 1 investigated the effect of valid and invalid physical cue as compared to baseline (without cue) in pain evaluation task (evaluating the pain intensity of a facial expression, N = 28). Experiment 2 employed eye-tracking to investigate the attentional process in valid and baseline conditions (evaluating the pain intensity of a body image with an apparently injured arm or leg, N = 65). We found the evaluation of pain intensity was the highest in the valid condition, and higher in baseline condition than invalid. As for eye-tracking results, children fixated more quickly, had more fixations and longer total fixation duration in valid-cue condition. Of attention allocation, compared with baseline condition, children fixated on arm/leg more quickly, more frequently and for longer time in valid condition. Additionally, eye-tracking results were significantly related to their evaluation of pain intensity.